Harmonization of Regulations in Realizing Legal Certainty for the Protection of Medical Records and Personal Data - Widiarta, I Nyoman; Jayantiari, I Gusti Agung Mas Rwa; Aryani, Luh Nyoman Alit (Dinasti Research, 2025)
This research is a normative legal study aimed at analyzing the norms governing the protection of patients' medical records under Law Number 17 of 2023 on Health and Law Number 27 of 2022 on Personal Data Protection, as a doctrinal review of related legislation. The method used is a juridical-normative approach through library research of statutory regulations, article explanations, legal doctrines, and secondary legal literature to explore the principles, rights, and obligations of data subjects and controllers. The normative analysis highlights the alignment of the principle of medical record confidentiality as stipulated in Article 177 paragraph 1 of Law Number 17 of 2023 on Health and the obligation to maintain the confidentiality of Personal Data under Article 36 of Law 27/2022, as well as patients’ right to access as regulated in Article 276 of Law 17/2023. The research findings identify an overlap between the long-term retention provisions of medical records and the